Ferroelectric and dielectric properties of sub-10 nm BaTiO3 nanoparticles - Fei Hao; Xin Liu; Jinyao Zhu; Wenyong Gan; Feiqiao He; Limin Guo; Yanan Hao (Journal of Asian Ceramic Societies)
BaTiO3 has been investigated nearly several decades due to its excellent ferroelectric and dielectric properties. However, the property evolution of BaTiO3 with a particle size of sub-10 nm is still unclear because of the difficulty during the fabrication and characterization. Here, a series of BaTiO3 nanoparticles with the average particle sizes of 2.8, 4.5 and 8.1 nm are achieved, and their phase structure, ferroelectric and dielectric properties are skillfully characterized. With the particle size decreasing from 8.1 to 2.8 nm, the nanoparticles show a declining non-centrosymmetry, nonlinear response, ferroelectricity and dielectric constant. Nevertheless, the 2.8 nm BaTiO3 nanoparticles still possess observable second harmonic generation, ferroelectric polarization switching behavior and butterfly loop, showing weak but distinguishable ferroelectricity. This research depicts a detailed ferroelectric and dielectric property evolution in sub-10 nm BaTiO3 nanoparticles, which provides theoretical basis and promising candidate for the future ferroelectric applications.